Rekontruksi Kriteria Visibilitas Hilal Serta Dampak Implementasi Kriteria Imkanurukyah MABIMS Baru Dalam Kemaslahatan - Ridhokimura Soderi; Darlius Darlius; Riza Afrian Mustaqim (Islamic Astronomy Department, Sharia and Law Faculty, 2024)
The aim of this research is to look at several existing hilal visibility criteria and see the extent of the impact that occurred after the implementation of the new MABIMS imakunurukyah criteria. In this research the author uses qualitative research with library data sources (library research) using qualitative descriptive analysis techniques where in this research the author describes in detail the existing criteria for visibility of the new moon and explains the impact of implementing the new MABIMS criteria from the perspective of ushul fiqh rules. The results of this research have the impact of applying the new MABIMS criteria to provide wider benefits in that at least we as Indonesian Muslims are moving forward in thinking about abandoning the old criteria which are no longer in accordance with the development of the world of astronomical science. Even with the implementation of the new MABIMS criteria, there are still differences in starting and ending the month of Qomariyah between Islamic organizations and the government. Differences will still be unavoidable if there is no agreement on the criteria used in determining the start of the Qomariyah month.